SWOT-THE ESSENCE AND METHODOLOGICAL PROBLEMS OF ANALYSIS - Togayev, Salim; Zayniddinova, Diyora (Educational Research in Universal Sciences, 2023)
The article considers the methodology for the implementation of SWOT – analysis. The article also presents methodological problems identified on the basis of the results of the study and proposals for their elimination.